Gender variables associated with female self-poisoning - Jack , R. L. (Cranfield University, 1989)
Self-poisoning - the deliberate, non-fatal ingestion of medicinal agents in excess of the recommended dose - is characterised wherever it occurs in Western society by a predominance of women - usually in the order of 2:1, and in over 60% of cases psychotropic medication is employed. Despite this the largely female nature of the phenomenon and its relationship to the 2:1 excess of women among the recipients of psychotropics generally has been virtually ignored in the literature. For many years self-poisoning was regarded as 'failed suicide' and consequently theoretical approaches to it have been dominated by the assumption of pathology - justifiable, perhaps in relation to completed suicide, as there is evidence of significant psychopathology among its perpetrators, but less so among self-poisoners where there is little such evidence. This thesis proposes that not only is the 'pathology paradigm' at odds with the known facts of self-poisoning but that the emphasis on psychopathology has discouraged the development of any convincing theory of female self-poisoning.An alternative account, based not upon pathology but upon processes of normative socialisation, suggests that the sex role system promotes a stereotypic view of women as helpless, dependent and emotionally unstable. This stereotype, when shared by physicians and their female patients, contributes to the excess prescription of psychotropic medication to women who have social, rather than psychopathological problems. Additionally, the sex role system and the social relations based upon it, fosters a 'female' cognitive style - particularly among those women who predominate among self-poisoners i.e. young, working class women with a history of family breakdown. This leads them to attribute the cause of adverse events internally to enduring, and irremediable personal inadequacy rather than - to others or misfortune. Such an "attributional style" externally renders these women vulnerable to "learned helplessness" in such circumstances - to the debilitating belief that their actions will be ineffective in resolving their difficulties. Female self-poisoning is interpretted, not as symptomatic of psychopathology, but as both consequence and expression of this socialised helplessness. The attributional style of male and female self-poisoners is compared in a pilot study with that of other patients and non-patients and support is found for an attributional approach to female self-poisoning.